(untitled) (ENTHYMEMA, 2017)
During the last decades, prose anthologies acquired great importance within the Italian publishing system. Starting from the specific case of the small and independent publishing house Minimum Fax, this essay analyzes prose anthologies as tools for the construction and the consolidation of relations and practices within the Italian literary field. A relational analysis of the productive practices that lay beyond the publishing of such anthologies allows to give reason of the structure that substantiates the production of these peculiar products, avoiding traditional approaches that tend to see anthologies as mere instruments for the creation of the literary canon.